Upaya Meningkatkan Tanggung Jawab Akademik Mahasiswa Manggarai Universitas PGRI Kanjuruhan Malang Melalui Konseling Kelompok Realita - Bergita Dewirati Juita; Romia Hari Susanti; Devi Permatasari (JKI (Jurnal Konseling Indonesia), 2021)
Academic responsibility is the attitude of individual behavior in carrying out their academic obligations. This academic obligation is in the form of tasks in academics, such as studying, doing assignments / doing exams by yourself, not procrastinating in doing assignments and being diligent in attending lectures.This study aims to determine the effectiveness of Reality Group Counseling to Improve the Academic Responsibility of Manggarai Students at Kanjuruhan University Malang. This study used a pre-experimental design with the type of one group pre-test and post-test design and the technique of taking the research subject was purposive sampling. The data analysis in this study used statistical-nonparametric with the Wilcoxon sign level test (Wilcoxon's signed rank test), which was processed with the help of SPSS 22.0 For Windows.The results of the Wilcoxon test analysis from the calculation results can be concluded that the Zhitung is -2.371 and the sig (2-tailed) is 0.018. if probability> 0.05 then Ho (zero hypothesis) is accepted, H1 (alternative hypothesis) if probability <0.05 then Ha is rejected then HO (zero hypothesis) is rejected and H1 (alternative hypothesis) is accepted. So the Wilcoxon test results show that sig (2-tailed) 0.018 <0.05 means that reality group counseling is effective in increasing student academic responsibility.